Dream recall frequency: Stability and changes assessed in a longitudinal design - Schredl, Michael; Gilles, Maria; Wolf, Isabell Ann-Cathrin; Peus, Verena; Scharnholz, Barbara; Sütterlin, Marc; Bardtke, Svenja; Send, Tabea; Deuschle, Michael (International journal of dream research, 2020)
Dream recall frequencies exhibit large inter-individual differences, ranging from recalling a dream almost every morning to recalling a dream almost never. Although dream recall has been conceptualized as a stable trait, longitudinal studies in this area are scarce. Within the framework of a complex study, 279 women (mean age: 31.76 ± 4.73 yrs.) completed a brief sleep questionnaire three times (last trimester of their pregnancy, 6 month postpartum, and 4 years postpartum) that included a dream recall frequency scale. The findings indicate that dream recall frequency is quite stable over the four-year period, although the correlation coefficients were somewhat smaller compared to previous studies - probably reflecting the effect of major life transitions (pregnancy, giving birth, caring for small children). The lowest dream recall at 6 month postpartum was not explained by sleep variables (sleep duration, nocturnal awakenings) and favors the hypothesis that interest in dream that might have been low while caring for very small children and this might explain long-term changes in dream recall.
Gesehen am 21.10.2020